Nickel-Catalyzed Paired Electrochemical Cross-Coupling of Aryl Halides with Nucleophiles - Zhang, Yong; Sun, Wenxuan; Li, Chao (Synthesis, 2021)
Electrochemistry has recently gained increased attention as a versatile strategy for achieving challenging transformations at the forefront of synthetic organic chemistry. However, most electrochemical transformations only employ one electrode (anodic oxidation or cathodic reduction) to afford the desired products, while the chemistry that occurs at the counter electrode yields stoichiometric waste. In contrast, paired electrochemical reactions can synchronously utilize the anodic and cathodic reactions to deliver the desired product, thus improving the atom economy and energy efﬁciency of the electrolytic process. This review gives an overview of recent advances in nickel-catalyzed paired electrochemical cross-coupling reactions of aryl/alkenyl halides with different nucleophiles.1 Introduction2 Nickel-Catalyzed Cross-Coupling Reactions2.1 C–C Bond Formation2.2 C–N Bond Formation2.3 C–S/O Bond Formation2.4 C–P Bond Formation3 Conclusion
Keywords: electrochemistry; paired electrolysis; nickel catalysis; cross-coupling; redox neutral reactions